International cooperation in the implementation of human rights and foreign policy of the Republic of Uzbekistan - Abdusalomov Mirabbos,; Muzaffarov Ikromjon Nodirbek ogli, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article discusses the implementation of cooperation of human rights and foreign policy of the Republic of Uzbekistan and the laws adopted on it, as well as articles of the Constitution of the Republic of Uzbekistan.